2002
DOI: 10.1023/a:1014615517996
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to determine the electrophysiological changes in patients using the anti epileptic drug vigabatrin and to correlate these findings with the previously reported risk for visual field loss in these patients. In 1998 the neurologists of both involved hospitals referred all patients on vigabatrin medication for ophthalmological examination to the outpatients clinics. Of the 33 patients whom were referred to our outpatient clinics, four had to be dropped from the study because of disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Recently, Moskowitz et al used electroretinography to identify worsening vision among pediatric patients taking the drug and concluded that ERG testing alone may be insufficient for this purpose [6]. In addition to the ERG, sweep visual evoked potential (VEP) testing has shown promise as a tool for monitoring pediatric patients taking vigabatrin [4], [7]. Nevertheless, the mechanism of the drug’s toxicity is still poorly understood, leading to a gap in our knowledge of how to prevent its vision loss side effect in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Moskowitz et al used electroretinography to identify worsening vision among pediatric patients taking the drug and concluded that ERG testing alone may be insufficient for this purpose [6]. In addition to the ERG, sweep visual evoked potential (VEP) testing has shown promise as a tool for monitoring pediatric patients taking vigabatrin [4], [7]. Nevertheless, the mechanism of the drug’s toxicity is still poorly understood, leading to a gap in our knowledge of how to prevent its vision loss side effect in patients.…”
Section: Introductionmentioning
confidence: 99%
“…As many as 40% of patients taking VGB, in controlled studies, have experienced irreversible visual field loss as measured by amplitude decreases of both the photopic electroretinogram (ERG) β-wave and the 30 Hz flicker response. 13 Additional clinical pathologies include abnormal macular reflexes, surface wrinkling retinopathy, and narrowed retinal arteries. 1 …”
Section: Introductionmentioning
confidence: 99%
“…This 2-year study (NCT00144300) compared ophthalmologic safety of immediate-release (IR) pramipexole and ropinirole in early idiopathic PD, adapting a comprehensive ophthalmologic assessment (COA) previously developed for vigabatrin [12, 13]. …”
Section: Introductionmentioning
confidence: 99%